INFLUENCE OF ISLAMIC TEACHINGS ON THE ATTITUDE OF STUDENTS TOWARDS EXAMINATION MALPRACTICES IN NIGERIA - Luqman Lakan Adedeji (Journal of Islamic Studies and Humanities, 2022)
Education is meant to nurture man to make of nature what can enable him make the society much better for him and for all. At every stage of this grooming process, however, examination still remains the major benchmark of cognitive competence and intellectual prowess right from the kindergarten to the university. Though, the application of the learning to solving real-life situation challenges in the society is what the world craves today. In several nations, examination is still skewed towards the test of retention ability than the appreciation of expertise in skills. This preference makes the process less vital than the product in the minds of the learners: the end justifies the means. Therefore, a number of learners in the society wouldn’t mind going to any length to have good results that will boost their employment opportunity or enhance their status in the society. Ideally, the importance of process in determining the value of the product should never be overlooked.  Though, things are changing for the better and several employers now value academic qualifications with adequate skills, a number of the learners are still of the opinion that good academic results only are synonymous to employability skills that open all doors to success. With the rapid technological advancement in the world today, examination malpractice has assumed more complex forms as it appears in different colours that often mesmerise those who advocate its demise. Using the examinee’s flesh as reference sheets and making the apparel as equally susceptible to manipulative innovation as any electronic device or bodily sign are just a tip of the iceberg. Hence, the war against examination malpractice often seems to be several paces behind in matching the sophistication of the perpetrators of the menace. Yet, it is a must-win war and efforts must continue towards making it a reality as soon as possible. The study employs primary and secondary sources of information, and they both reflect a great mismatch of efforts and resources in the war against examination malpractice in Nigeria. It was found out that lack of adequate knowledge of the nature and mechanism of the menace often leaves loopholes for the perpetrators to carry out their plans. Another finding is that the perpetrators are close to being in abreast with technology while the army against them is more analogous than technological. Inconsistency in implementing the deterrent policies also encourages the perpetrators. The study therefore recommends strict compliance with Islamic teachings and stiffer measures against offenders amongst others.